Artificial Intelligence in Emerging Narratives: Risk Communication in Dynamic Video Games - Cristian Giovanni Castrillón Arias, Julio César Caicedo Eraso, Diana Varon-Serna (Journal of International Crisis and Risk Communication Research, 2024)
The implementation of artificial intelligence (AI) in dynamic video game design has transformed the way players experience and perceive risks within narratives. This article discusses how AI can be used to structure and communicate risks in emerging narratives, improving user immersion and engagement. A mixed methodological design was used that included the analysis of contemporary video games and interviews with developers and players. The results reveal that AI techniques can lead to more realistic interactions and a deeper understanding of players' decisions in the face of risks. It is concluded that AI represents an invaluable resource for the narrative evolution of video games and their educational potential.